Perception of College Students in Papua Province on Plagiarism - Rahmawansyah Sahib; Ira Eka Pratiwi; Fachrudin Fiqri Affandy; Amirullah Amirullah (Al-Mudarris: Journal Of Education, 2022)
Plagiarism is serious misconduct for all of the academicians in the world, including Papua, Indonesia. This paper aims at exploring the Papuan students’ perceptions on plagiarism. This paper focused on the students’ knowledge on plagiarism, the students ‘experience in plagiarism, and the strategy to avoid plagiarism. This paper employed a descriptive qualitative design investigating the students’ perception of plagiarism in Fattahul Muluk State Islamic Institute of Papua. The participants of this study were purposively selected from two faculties. There were seven students of the Faculty of Tarbiyah and seven Faculty of Islamic Economics and Business students, and the data were analyzed using discourse analysis. The results revealed that Papuan students’ perception on plagiarism due to three parts; 1) the students knew plagiarism as an act of copyright infringement, plagiarism is a crucial action, plagiarism is the act of copy-paste, plagiarism is an act that causes writers difficulty in developing their writing potential, and plagiarism is an act of theft, 2) The Plagiarism occurred when the students doing an assignment, they have lack understanding about the assignment’s instruction, sometimes reference sources are difficult to access, and the students pressed by the deadline for submission, and 3) The students avoid plagiarism through paraphrase then cite the sources, and used software like Mendeley and plagiarism checker.  However, further investigation is necessary to examine the relative contribution of Papuan students ‘perceptions on plagiarism practice.